The challenge of healthcare for vulnerable and marginalized populations - Camila Biazus Dalcin; Ana Karina Bezerra Pinheiro (Rev Rene)
Vulnerability, in the health context, emerged with the Human Immunodeficiency Syndrome (HIV) epidemic, when the factors and groups that would be associated with a higher prevalence of people with Human Immunodeficiency Virus were studied. Vulnerability highlights possible factors related to health conditions, thus differentiating itself from risk, since the latter is exclusively related to the chances of becoming ill of an individual or population.